Penerapan Metode MOOSRA Pada Sistem Pendukung Keputusan Pemilihan Leader Produksi - Nainggolan, Dian Wichita; Utomo, Dito Putro (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
The selection of production leaders at PT. Sagami Indonesia is determined based on the scores obtained from each criterion set by the company. However, choosing a leader is not easy due to the presence of many candidates meeting the criteria, and the results obtained are still less effective because there is no strong regulation in the process. To address this issue, there is a need for an assessment using a Decision Support System application to assist in decision-making for selecting production leaders. Subsequently, the analysis is conducted using the MOOSRA method to obtain rankings based on the final scores of alternatives. Based on the test results, it can be concluded that the Decision Support System application for leader selection, using the MOOSRA method, can help prevent fraud in the production leader selection process.